Advantage of fundus first method over conventional approach in difficult laparoscopic cholecystectomy: a prospective study - Mishra, Braja Mohan; Guru, Rabi Narayana; Kar, Sunil Kumar (International Surgery Journal, 2019)
Background: Fundus first method is a widely accepted and practiced procedure in open cholecystectomy to deal the difficult cases but laparoscopic surgeons still have reserved opinion regarding use of fundus first approach in difficult laparoscopic cholecystectomy (DLC). As in open cholecystectomy fundus first laparoscopic cholecystectomy (FFC) can have advantages over conventional laparoscopic cholecystectomy (CLC) in DLC. So many preoperative, intraoperative, postoperative information were collected in both CLC and FFC and compared to evaluate whether FFC has any advantage over CLC in difficult laparoscopic cholecystectomy. Methods: A total 73 cases were included in the study that underwent laparoscopic cholecystectomy (LC) for gall stone diseases and intraoperatively found to be difficult cases. They were distributed into 4 classes i.e. Class I, Class II, Class III and Class IV according to the type of difficulty encountered during surgery. Results: Out of the 73 patients 24 were male and 49 were Female. Age of patient ranged from 14 to 70 years with mean age of 42.64 years. Out of 38 cases operated with FFC 6 cases (15.78%) needed conversion to open cholecystectomy as compared to 26 out of 35 (71.14%) cases that underwent CLC where conversion was done. Mean duration of hospital stay is 4.19±3.053. Mean hospital stay in FFC is 2.58±1.869 days and that of CLC is 5.14±3.143 which is clearly much higher and statistically significant (p< 0.001) than mean hospital stay in case of FFC. Conclusions: FFC has advantages over CLC in difficult LC i.e. reduced conversion rate, lesser hospital stay and less duration of antibiotic use.